2009
DOI: 10.1007/s10558-009-9083-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Pulmonary System Impedance and Right Ventricular Function in Normal Sheep

Abstract: Right ventricular (RV) afterload is a key determinant of RV function and is increased in many cardiopulmonary pathologies. Pulmonary circulation input impedance has been used to quantify afterload previously but due to its complexity has not been widely applied. This study examines the effect of a subset of the impedance spectrum, the zeroth and first harmonic impedance moduli (Z (0), Z (1)), on RV performance in large animals. An artificial circuit with adjustable resistance and compliance (C) was implanted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Kuo et al . 6 confirmed that Z 0 is the key determinant of RV output in their study examining the effect of pulmonary system impedance on CO. For every 1 mmHg/(L/min) increase in Z 0 , there is an approximate 3.65% decrease in CO. Likewise, for every 1 mmHg/(L/min) increase in Z 1 , there is a 0.08 Z 0 % decrease in CO.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Kuo et al . 6 confirmed that Z 0 is the key determinant of RV output in their study examining the effect of pulmonary system impedance on CO. For every 1 mmHg/(L/min) increase in Z 0 , there is an approximate 3.65% decrease in CO. Likewise, for every 1 mmHg/(L/min) increase in Z 1 , there is a 0.08 Z 0 % decrease in CO.…”
Section: Introductionmentioning
confidence: 63%
“…1,11 The most physiologically relevant impedances in this setting are those at the zeroth and first harmonic frequencies. 5,6 These represent, respectively, the opposition to blood flow that is steady and periodic at a frequency equal to the heart rate. Moreover, cardiac output (CO) during TAL attachment is affected mostly by the magnitude of the zeroth and first harmonic impedance moduli ( Z 0 and Z 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may not be uniform with increasing body size, and the short axis function may be more prominent in smaller individuals (14). The influence of afterload on SЈ was evident and in keeping with others (15)(16)(17).…”
Section: Discussionmentioning
confidence: 62%
“…This index is a preferred index of afterload by physiologists due to its independence from cardiac function [4] and because it includes blood flow resistance due to left atrial pressure. Thus, it is less commonly referred to as the “total peripheral resistance.” Previous studies by our group have indicated that this is an excellent index for predicting right ventricular function under high afterload states [5,6]. …”
Section: Methodsmentioning
confidence: 99%
“…Kim et al [5] and Kuo et al [6] studied this relationship previously for sheep at resting CO. They both found that sheep with larger baseline CO had larger changes in CO for a given increase in Z 0 .…”
Section: Commentmentioning
confidence: 99%